Molecular tumour board at European Institute of Oncology: Report of the first three year activity of an Italian precision oncology experience. (April 2023) - Repetto, Matteo; Crimini, Edoardo; Boscolo Bielo, Luca; Guerini-Rocco, Elena; Ascione, Liliana; Bonfanti, Andrea; Zanzottera, Cristina; Mazzarella, Luca; Ranghiero, Alberto; Belli, Carmen; Criscitiello, Carmen; Esposito, Angela; et al.
Abstract: Background: Precision oncology aims to improve clinical outcomes by personalising treatment options for patients with cancer. Exploiting vulnerabilities identified in a patient's cancer genome requires reliable interpretation of a huge mole of alterations and heterogeneous biomarkers. ESMO Scale for Clinical Actionability of Molecular Targets (ESCAT) allows evidence-based evaluation of genomic findings. Molecular tumour boards (MTBs) convey the required multi-disciplinary expertise to enable ESCAT evaluation and strategical treatment choice. Materials and method: We retrospectively reviewed the records of 251 consecutive patients discussed by European Institute of Oncology MTB between June 2019 and June 2022. Results: One-hundred eighty-eight (74.6%) patients had at least one actionable alteration. After MTB discussion, 76 patients received molecularly matched therapies (MMTs) while 76 patients received standard of care. Patients receiving MMT displayed higher overall response rate (37.3% versus 12.9%), median progression-free survival (mPFS 5.8 months, 95% confidence interval [CI] 4.1–7.5 versus 3.6 months, 95% CI 2.5–4.8, p = 0.041; hazard ratio 0.679, 95% CI 0.467–0.987) and median overall survival (mOS 35.1 months, 95% CI not evaluable versus 8.5 months, 95% CI 3.8–13.2; hazard ratio 0.431, 95% CI 0.250–0.744, p = 0.002). Superiority in OS and PFS persisted in multivariable models. Among 61 pretreated patients receiving MMT, 37.5% of patients had PFS2/PFS1 ratio ≥1.3. Patients with higher actionable targets (ESCAT tier I) had better OS (p = 0.001) and PFS (p = 0.049), while no difference was observed in lower evidence levels. Conclusions: Our experience shows that MTBs can yield valuable clinical benefit. Higher actionability ESCAT level appears to be associated with better outcomes for patients receiving MMT. Highlights: Precision oncology aims to improve clinical outcomes by personalising treatments. Molecular tumour boards catalyse multi-disciplinary expertise for precision oncology. European Institute of Oncology molecular tumour board discussed 251 patients in its first three year activity. Patients receiving targeted therapies have superior survival outcomes. Higher ESMO Scale for Clinical Actionability of Molecular Target tiers alterations derive greater benefit from target therapies.